Low cost and time efficiency in investment projects in Arequipa and Moquegua 2004 - 2020 - Flores Arocutipa, Javier Pedro; Jinchuña Huallpa, Jorge; Cornelio Aira, Rocío Claribel; Chacolla Soto, Moisés; de la Paz Ramos, José Miguel; Fernández Sosa, Luís Enrique (Political Questions, 2021)
Objective: To demonstrate the low efficiency in costs and timeframes in 22 investment projects (PIP) of the Regional Government of Moquegua and Arequipa, which generated higher costs and timeframes between the ex ante and ex post in the period 2004-2020. Method: Inductive, basic, not experimental. Results: Based on the Wilcoxon test, it was shown that the costs of 12 projects in Moquegua, before and after, were different with asymptotic significance (bilateral) 0.006, from 127 to 220 million; and the “t” test for related samples generated the significance (bilateral) of 0.000. It was observed that the average calculated in days was different, that the average of the ex ante period turned out to be 339 days while the average of the actual period was 2307 days. In 10 projects in Arequipa, the Wilcoxon test generated 0.007 and the costs went from 1030 to 1585 million soles; the difference in terms generated a p-value of wilcoxon of 0.004 from an average of 15.4 to 57.5 months. Conclusion: The costs of the previous and subsequent period are different, as are the proposed deadlines and actual deadlines in both regions.